An Improved Method of Failure Mode Analysis for Design Changes - Laurenti, R.; Rozenfeld, H. (Cranfield University Press, 2009)
Customers and market changes behaviour are a large part of the product creation and modification. Though, design changes introduce new potential failures into the products. In this paper, it is presented an integrated method which turns attention to the analysis of design changes. The method is based on FMEA and DRBFM methods, and on remarks from four focused interviews. The interviews showed the necessity of a structured process of managing engineering changes, multidisciplinary work, empowerment of responsibilities, committed personnel and understanding of the modifications. Yet, further work must be undertaken to assess and validate the novel method.
Organised by: Cranfield University
Keywords: Failure Analysis; Design Changes; FMEA; DRBFM